Traces of colonialism in english language teaching (ELT) materials: a raciolinguistic justice exploration of decolonizing ELT curricula - Ramirez Quimbayo, Maria Camila (Kansas State University, 2024)
Decolonizing world language education represents a multifaceted approach that questions some traditional pedagogies in foreign, second, and heritage language contexts. This current trend challenges monoglossic ideologies, western thought, and stereotypes that perpetuate harmful narratives about minoritized linguistic groups while seeking to embrace diverse perspectives, value linguistic diversity, and ensure the inclusion of multiple cultural identities and communities. Therefore, the process of transforming world language education practices requires didactic materials to be thoroughly analyzed to create awareness of the need for decolonizing language education. Thus, the current research study, rooted in Raciolinguistic Justice, primarily aims to identify if there are traces of colonial ideologies in English Language Teaching (ELT) curricula and materials at the college level. Additionally, this study will exemplify to what extent raciolinguistic justice frameworks can be employed to thematically categorize and analyze the crossways of language, race, and education in the representation of decolonizing epistemologies within language education. Furthermore, a sample lesson will be provided for language instructors to be equipped to make pedagogical decisions to decolonize language education. A thorough analysis of the intersection of language and race in ELT materials will be carried out, to evaluate the hypothesis that most world language teaching materials are embedded in colonial ideologies that prioritize monolingualism, Eurocentric thinking, and white speech.
Keywords: Raciolinguistics; Social justice; English language teaching; Translanguaging; Decolonization; Colonialism